Media IQ Interactive Games Assessment Using a Contextual Teaching Learning (CTL) Approach to Improve Primary School Students' Critical Thinking Ability - Yovita; Mery Berlian; Alaniyah Syafaren (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Primary school students' critical thinking skills currently face significant obstacles, mainly due to constraints on teachers' pedagogical skills, which include the use of learning methods and models, classroom practice. The aim of this research is to utilize industry 4.0 technology, one of which is an educational game based on IQ Interactive. The important urgency in developing this media is based on research by that educational games can improve students' cognitive abilities. The benefit of learning using the CTL method is changing the conventional learning system to a modern one. This research is development research (Research and Development), the development of IQ Interactive Games was carried out using the CTL Approach using the ADDIE development model. The results of the IQ Games Interactive research showed that the majority of respondents responded positively to the use of IQ Games Interactive, including ease of use, layout, access to information, effectiveness, text presentation, use of QR, color composition, systematics and efficiency. Aspects of readability and understanding of concepts are very important in assessing the quality of media, including IQ Interactive Games